Penerapan Model Pembelajaran Kooperatif Tipe Numbered Heads Together (Nht) Terhadap Hasil Belajar Tik Kelas Vii Di Smp Mataram Semarang - Adyria, Fellisia Stefani; Andrasto, Tatyantoro (Jurusan Teknik Elektro Universitas Negeri Semarang, 2017)
The purpose of the research is to determine improving student learning outcomes and student activity and creating innovative learning model NHT cooperative. Design of the research using quasi experimental. Population of the research are grade VII SMP Mataram Semarang students, school year 2015/2016. Sample of the research has been taken using simple random sampling technique, in order to obtain students of class VII B (experiment group) and students of class VII C (control group). Data analysis technique used prerequisite analysis covering normality and homogeneity test, and hypothesis test covering the different and gain test. The research results show that the average value of student learning experiment group is 83,18 and the control group is 61,14. The hypothesis test shows that there are significant differences of learning outcomes between experiment and control group students. Learning outcomes of experiment group students are higher than the control group proven with gain indeks of experiment group is 0,71 compared with gain indeks of control group is 0,30. Based on the hypothesis test, can be concluded that the application of cooperative learning type NHT is proven student learning outcomes and student learning activeness. Researcher Suggestion is teacher be able to apliccation model cooperative learning type NHT as alternative learning to upgrading if the student have low learning outcomes.